Engineering a Reduced Escherichia coli Genome - Kolisnychenko, Vitaliy; Plunkett, Guy; Herring, Christopher D.; Fehér, Tamás; Pósfai, János; Blattner, Frederick R.; Pósfai, György (Genome Research, 2002)
Our goal is to construct an improved Escherichia coli to serve both as a better model organism and as a more useful technological tool for genome science. We developed techniques for precise genomic surgery and applied them to deleting the largest K-islands of E. coli, identified by comparative genomics as recent horizontal acquisitions to the genome. They are loaded with cryptic prophages, transposons, damaged genes, and genes of unknown function. Our method leaves no scars or markers behind and can be applied sequentially. Twelve K-islands were successfully deleted, resulting in an 8.1% reduced genome size, a 9.3% reduction of gene count, and elimination of 24 of the 44 transposable elements ofE. coli. These are particularly detrimental because they can mutagenize the genome or transpose into clones being propagated for sequencing, as happened in 18 places of the draft human genome sequence. We found no change in the growth rate on minimal medium, confirming the nonessential nature of these islands. This demonstration of feasibility opens the way for constructing a maximally reduced strain, which will provide a clean background for functional genomics studies, a more efficient background for use in biotechnology applications, and a unique tool for studies of genome stability and evolution.[Sequence data described in this paper have been submitted to the DNA Data Bank of Japan, European Molecular Biology Laboratory, and GenBank databases under accession nos. AF402780,AF402779, and AF406953, respectively.]